2017 13th IEEE International Conference on Intelligent Computer Communication and Processing (ICCP) 2017
DOI: 10.1109/iccp.2017.8117042
|View full text |Cite
|
Sign up to set email alerts
|

Analysis, design and implementation of secure LoRaWAN sensor networks

Abstract: Abstract-LoRaWAN is a LPWAN (Low Power Wide Area Network) technology used in a large variety of Internet of Things (IoT) applications. The paper addresses the security concerns of data protection and data privacy in sensor networks that make use of the LoRaWAN (Long-Range Wide Area Network) protocol specification. In this context, this paper performs an in-depth analysis of the security aspects in LoRaWAN sensor networks. Additionally, a novel secure LoRaWAN network architecture is proposed. The architecture p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Numerous research works showed the security vulnerabilities in LoRaWAN v1.0 [ 84 , 85 , 86 , 87 , 88 , 89 ]. Considered security vulnerabilities include the replay attack of join-request packet for OTAA, data packet replay attack in case of ABP, eavesdropping of data packets in ABP case, bit flipping attack between network server and application server, ACK spoofing, etc.…”
Section: Mac Layer Performance Evaluationmentioning
confidence: 99%
“…Numerous research works showed the security vulnerabilities in LoRaWAN v1.0 [ 84 , 85 , 86 , 87 , 88 , 89 ]. Considered security vulnerabilities include the replay attack of join-request packet for OTAA, data packet replay attack in case of ABP, eavesdropping of data packets in ABP case, bit flipping attack between network server and application server, ACK spoofing, etc.…”
Section: Mac Layer Performance Evaluationmentioning
confidence: 99%
“…There are only a few studies address the LoRaWAN security [80,81]. Studies focus on the most important and the least secure stages of the LoRaWAN network protocol which is activation process [82].…”
Section: Securitymentioning
confidence: 99%
“…Also, the communication between the end devices and the rest of the network can be destroyed. To provide secure data transmission, an authentication mechanism for the gateways is necessary in order to prevent the network from attacks [ 97 ].…”
Section: Research Challenges and Recommendations For Future Workmentioning
confidence: 99%